Concentration dependent properties lead to plastic ratcheting in thin island electrodes on substrate under cyclic charging and discharging. (1st February 2019) - Guo, Kai; Zhang, Wei; Sheldon, Brian W.; Gao, Huajian
Abstract: It is known that the mechanical properties of electrodes in lithium-ion batteries, such as modulus, yield stress, and interfacial strength, can depend strongly on lithium concentration. Here we show that a thin film island electrode with properties dependent on lithium concentration naturally undergoes plastic ratcheting with accumulative deformation and failure during cyclic charging and discharging. Some key predictions from numerical simulations are validated by galvanostatic tests. Strategies to avoid ratcheting include limiting the electrode size and/or selecting a balanced combination of concentration dependent materials properties. Graphical abstract: Image 1